Research on the emotional communication mechanism of digital news - Li, Xiao; Mahamed, Mastura; Bidin, Rosmiza (Redfame Publishing, 2025)
As emotional communication gains prominence in digital news production, scholars have increasingly re-examined its relationship with news objectivity. This study investigates how digital technology transforms emotional communication mechanisms, particularly focusing on their narrative and mobilization strategies. Through case analysis and sentiment analysis of 295 award-winning works from the China News Award, the research identifies key mechanisms: voice narratives and positive emotional rhetoric that cultivate specific atmospheres, alongside empathy, personalization, and immersive mobilization that expand audiences' "emotional imagination." On a practical level, emotional communication is reshaping digital journalism by profoundly influencing production, circulation, and audience engagement. Theoretically, it broadens the epistemological and methodological scope of digital journalism, offering guidance for the industry to evolve toward a "human emotional civilization."